HOW TALK SHOW PRESENTER USING CODE MIXING AND CODE SWITCHING ON TV PROGRAM IN INDONESIA - Abbas, Aswin; Setiawan, Hasrat Indar (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2020)
This research aims to investigate the types and dominant types of code mixing and code switching used by talk show presenters when they are on air on TV programs. This research used mix method with QUAL-Quan Model, Qualitative method is dominant used than quantitative method. The subject in this research was 8 talk show presenters which is familiar and famous arround the viewers. The instrument of this research was documentation as the instrument. After conducting the research, finally the researcher find that (1) Related to code mixing types from presenters, there are 148 code mixings from five types. Those are 66 code mixings in the form of word insertion, 45 code mixings in the form of phrase insertion, 1 code mixing in the form of idiom insertion, 29 code mixings in the form of hybrid insertion, and 7 code mixings in the form of reduplication insertion. Meanwhile, there are also 59 code switchings in three types. Those are 9 tag switchings, 24 inter sentential switchings, and 26 intra sentential switchings. (2) Then, the dominant type of code mixing is code mixing in the form of word insertion (44.59%) and the dominant type of code switching is intra sentential switching (44.06%). The other finding of this research is male presenters more often used code mixing than female. Otherwise female presenters more often used code switching than male presenters